2016
DOI: 10.1002/smll.201503292
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoplatform with Precise Control over Release of Cargo for Enhanced Cancer Therapy

Abstract: The development of a nanocarrier delivery system having both sufficient stability in blood circulation and a rapid drug release profile at target sites remains a major challenge in cancer therapy. Here, a multifunctional star-shaped micellar system with a precisely spatiotemporal control of releasing encapsulated agents is developed by mixing a photoinitiated crosslinking amphiphilic copolymer with a phenylboronic acid (PBA)-functionalized redox-sensitive amphiphilic copolymer for the first time. The combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 66 publications
1
52
0
Order By: Relevance
“…Additionally, the active targeting micelle‐containing group, DOX‐PM+AP@F, had a slightly stronger fluorescence intensity than that of DOX‐M+AP@F without active targeting, which may be ascribed to that the receptor‐mediated specific internalization of DOX‐loaded micelles. [12b,c,18] The corresponding CLSM images in Figure c are in agreement with the result of flow cytometry. In general, the dual drug–loaded hierarchical‐structured electrospun fiber can successfully codeliver drugs into the tumor cells and DOX accumulation can be increased with the help of AP, which would overcome the drug resistance of MCF‐7/ADR tumor cells.…”
Section: Resultssupporting
confidence: 81%
“…Additionally, the active targeting micelle‐containing group, DOX‐PM+AP@F, had a slightly stronger fluorescence intensity than that of DOX‐M+AP@F without active targeting, which may be ascribed to that the receptor‐mediated specific internalization of DOX‐loaded micelles. [12b,c,18] The corresponding CLSM images in Figure c are in agreement with the result of flow cytometry. In general, the dual drug–loaded hierarchical‐structured electrospun fiber can successfully codeliver drugs into the tumor cells and DOX accumulation can be increased with the help of AP, which would overcome the drug resistance of MCF‐7/ADR tumor cells.…”
Section: Resultssupporting
confidence: 81%
“…Meanwhile, the free HCPT group did not show a satisfactory tumor suppression efficacy, as the tumor volume was ≈0.87 cm 3 , which was 4.8 times as big as that of the PECL/DA‐Tat‐M group. In addition, the body weight of the mice treated with different samples all maintained an upward tendency (Figure c), reflecting that HCPT exhibited a relative lower systematic toxicity than some other antitumor therapeutics, such as doxorubicin . These results demonstrated that the therapeutic efficacy of PECL/DA‐Tat‐M was better than the other groups.…”
Section: Resultsmentioning
confidence: 77%
“…38,39 Compared with other sheddable micelles, the release of Dox for the rosin-based ssP micelles in the presence of 10 mM GSH appeared to be slower 46,47,50 or competitive. Upon the reductive cleavage of disulfide linkages at the core/corona interfaces in response to GSH, Dox-loaded micelles are destabilized.…”
Section: Resultsmentioning
confidence: 95%
“…13,14 A particular cellular trigger is the reductive reaction associated with the presence of glutathione (GSH). [37][38][39] Furthermore, such reductionresponsive detachment of hydrophilic coronas, particularly poly(ethylene glycol) (PEG), has been significantly explored for gene delivery applications where PEG-stabilized micelloplexes are interacted with nucleic acids. Besides such a large redox potential difference, the elevated concentration in cancer cells makes GSH an effective intracellular trigger for reduction-responsive degradable nanocarriers.…”
Section: Introductionmentioning
confidence: 99%